Fruits and Vegetables Used in Treating Respiratory and Other Troubles in Africa: Ethnopharmacology and Phytochemistry - Gumula, van; Buyinza, Daniel; Onen, Patrick; Kyarimpa, Christine (Springer Nature, 2025)
Respiratory troubles, which encompass conditions such as cough, asthma, tuberculosis, bronchitis, common cold, and chronic obstructive pulmonary disease, pose significant health challenges globally. This chapter explores the diverse array of biologically active agents (BAA) found in vegetables and fruit plants used not only as sources of food but also for treatment of respiratory troubles in Africa. A total of 38 vegetables and fruit plants from 22 families were encountered. The plants are sources of antimicrobials that help the lungs to resist infection as well as boost the immunity of the host; expectorants which stimulate the coughing up of mucus; anti-inflammatory agents and demulcents which soothe irritated membranes, while others are spasmolytic which relax the bronchial muscles. The BAA include allicin from garlic, quercetin from onions, theobromine from cacao, and anethole from fennel. BAA, such as bromelain in pineapple, beta-carotene in carrots, vitamin C in lemon, and glucosinolates in radish, play pivotal roles in mucolytic activities and enhancement of immune function as well as repair of the bronchial membrane. Some of the vegetables/fruits are a source of mineral salts that are vital to the integrity and functioning of lungs. Thus, Cleome gynandra contains selenium, a key component that inhibits HIV-associated tuberculosis. The available research evidence underscores the importance of integrating the BAA into human daily diets as a prophylactic approach and therapeutic strategy against respiratory troubles.